Dual fieldbus industrial IoT networks using edge server architecture. (April 2020) - Dirgantoro, Kevin Putra; Nwadiugwu, Williams-Paul; Lee, Jae Min; Kim, Dong-Seong
Abstract: This letter proposes dual fieldbus communication for Industrial Internet of Things using an edge server. Dual fieldbus communication implements a redundant fieldbus to prevent bus faults and increase the system's availability. The primary communication link uses Modbus while the redundant fieldbus is a Controller Area Network (CAN). When an error occurs, the protocol changes automatically to use the CAN bus because of its faster error recovery. It outperforms the conventional Modbus for both detected data error and data success rates. Meanwhile, the edge server implements a long short-term memory (LSTM) and performs 95 percent faster than processing in the cloud.